2015
DOI: 10.33158/asb.2015v1i1p39
|View full text |Cite
|
Sign up to set email alerts
|

Balance among calcium, magnesium and potassium levels affecting Asian Soybean Rust severity

Abstract: This work aimed to analyze the effect of the variation of the proportions of calcium in relation to the contentes of magnesium and potassium in the cationic capacity of change (CCC) of the soil, seeking to propitiate the  appropriate balance of bases, so that the soybean plants presented good nutritional state and had conditions of resisting to the attack of Phakopsora pachyrhizi Syd. & P. Syd. The experiment was driven in randomized blocks with eight replications and the treatments consisted of doses of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Most forecasting models use only environmental factors; these usually include hours of wetness and temperature, considering that the pathogen and host (the other vertices of the triangular disease), are always present (M. C. Alves, Pozza, Costa, Carvalho, & L. S. Alves, 2011). In addition, the models usually not consider factors such as leaf age and susceptibility (Xavier, Martins, Fantin, & Canteri, 2017) and plant nutrition (Gaspar et al, 2015). The present study demonstrated that the presence of inoculum (the pathogen vertex) exerts a great influence on epidemics during the season.…”
Section: Discussionmentioning
confidence: 83%
“…Most forecasting models use only environmental factors; these usually include hours of wetness and temperature, considering that the pathogen and host (the other vertices of the triangular disease), are always present (M. C. Alves, Pozza, Costa, Carvalho, & L. S. Alves, 2011). In addition, the models usually not consider factors such as leaf age and susceptibility (Xavier, Martins, Fantin, & Canteri, 2017) and plant nutrition (Gaspar et al, 2015). The present study demonstrated that the presence of inoculum (the pathogen vertex) exerts a great influence on epidemics during the season.…”
Section: Discussionmentioning
confidence: 83%